Methods of Selenium Application Differentially Modulate Plant Growth, Selenium Accumulation and Speciation, Protein, Anthocyanins and Concentrations of Mineral Elements in Purple-Grained Wheat - Xia, Qing; Yang, Zhenping; Shui, Yang; Liu, Xiaoli; Chen, Jie; Khan, Shahbaz; Wang, Jianming; Gao, Zhiqiang (Frontiers in Plant Science, 2020)
Selenium (Se) is an essential micronutrient for human health. Deficiency and suboptimality of Se in human populations are a potential health risk. The reduction of such health risk by biofortification of crops, particularly in wheat has drawn much attention, especially for color-grained wheat as it is rich in anthocyanins and can be used as a major source of antioxidants in diet. Herein, a two-year field study on the purple-grained wheat cultivar (202w17) and common wheat cultivar (Shannong 129) was conducted with soil application (SeS) and foliar spray (SeF) of selenium. Results showed that the SeS increased shoot dry weight and grain yield. Both SeS and SeF enhanced the concentration of organic Se, but the higher concentration of organic Se in the grain of two cultivars was observed in SeF in comparison with SeS. The concentration of organic Se in the grain of 202w17 treated with SeF was approximately 1.5-fold of that in Shannong 129 with SeF. The analysis of Se accumulation in different parts of the plant revealed that 202w17 accumulated more Se in shoots and grain than Shannong 129, and 202w17 had also higher levels of total protein, total free amino acids and anthocyanin in grain than Shannong 129. In addition, SeF significantly increased the concentrations of zinc (Zn), calcium (Ca), magnesium (Mg) in both cultivars, but decreased the concentration of chromium (Cr), cadmium (Cd) and lead (Pd), which phenomenon was more significant in 202w17. Our results indicate that SeS increases plant growth, leading to higher grain yield in two cultivars tested. The purple-grained wheat (202w17) could accumulate more Se in grain and have a higher concentration of orgainic Se in grain than the common wheat (Shannong 129).